Heads Up Play: Acute Assessment and Management of Basketball-Related Craniofacial Injuries by On-Court Personnel. Issue 4 (1st June 2021) - Slavin, Benjamin R.; Pierrot, Randall G.; Sprau, Annelise C.; Wolfe, Erin M.; Mathew, Prakash J.; Chopra, Karan; Thaller, Seth R.
Abstract : Supplemental Digital Content is available in the text Abstract : Introduction: With a following of over 825 million people, basketball currently ranks amongst the world's most popular sports. Despite a number of concussion awareness and player safety protocols that have been implemented at the professional level of organized play, a standardized, layperson-friendly algorithm for the acute management of basketball-related craniofacial injuries does not appear to presently exist. Methods: This 10-year retrospective cohort study was conducted using the National Electronic Injury Surveillance System database to examine basketball-related craniofacial injuries from 2010 to 2019. Within the National Electronic Injury Surveillance System dataset, factors including patient age, gender, diagnosis, injury type, and injury location were included in our analysis. Results: Overall, 22, 529 basketball-related craniofacial injuries occurred between 2010 and 2019 in players ages 5 to 49 years old. Adolescent (12–18-year-old) and young adult (19–34-year-old) age groups had the highest incidence of craniofacial injuries. The adolescent cohort experienced a significantly greater proportion of concussions and lower proportion of both facial lacerations and fractures compared with the within group null hypothesis of equal proportions ( P < 0.05). The young adult cohort experienced a significantly greater proportion of facial lacerations and fractures and lower proportion of concussions, contusions/abrasions, hematomas, and internal injuries compared to this cohort's null hypothesis ( P < 0.05). Males experienced a significantly greater proportion of fractures, lacerations, and dental injuries and lower proportion of concussions, contusions/abrasions, and internal injuries compared to the hypothesized equality of proportions ( P < 0.05). Females experienced a significantly greater proportion of concussions, contusions/abrasions, and internal injuries and lower proportion of fractures, lacerations, and dental injuries compared to the hypothesized equality of proportions ( P < 0.05). Conclusions: Although several steps have already been taken at the professional level to try to promote player safety, particularly with concussion protocols and prevention of lower extremity injuries, there remains a paucity of resources to guide management of other types of acute craniofacial injury. The role of layperson-friendly educational interventions remains intriguing as a potential means of improving outcomes regardless of socioeconomic status or health literacy. Additional studies still need to be completed to determine efficacy and best future direction.